PENANGGULANGAN WABAH ANTRAKS DI KABUPATEN GUNUNGKIDUL BERDASARKAN PERATURAN DAERAH NOMOR 3 TAHUN 2016 KABUPATEN GUNUNGKIDUL TENTANG KEAMANAN PANGAN: Handling of Anthrax Outbreak in Gunungkidul Regency, Special Region of Yogyakarta Based on the Regional Regulation of Gunungkidul Regency Number 3 of 2016 on Food Safety - Afriyan Putra; Eko Primananda (Faculty of Law, Universitas Trisakti, 2025)
Health and food safety are among the concurrent affairs that fall under the responsibility of both the central and regional governments, as stipulated in Law Number 23 of 2014 on Regional Government. Regional autonomy allows each region to regulate and address its own affairs within the framework of government matters established by law. The anthrax outbreak in 2023 in Gunungkidul Regency, Special Region of Yogyakarta, is one such concurrent governmental matter in the fields of health and food safety. The spread of anthrax was caused by various factors, including the role of the regional government in preventing and managing the disease. In addressing this, the Gunungkidul regional government referred to Regional Regulation Number 3 of 2016 on Food Safety. Therefore, the identification of problems arising from the anthrax outbreak and the responsibility of the local government is how the Local Government’s Efforts are in dealing with the anthrax outbreak in Gunungkidul Regency, Special Region of Yogyakarta in 2023. The results of the research and conclusions carried out by the Gunungkidul Regency local government are in the form of preventive efforts and repressive efforts.